Estimation of the Bubble Point Pressure of Multicomponent Reservoir Hydrocarbon Fluids - Usen, Benjamin Sunday; Obi, Chidi (UI Scholars Hub, 2022)
This study developed a novel C-sharp (C#) programming language for the estimation of bubble point pressure (BPP) of various hydrocarbon mixtures at equilibrium state. The methodology was based on vapor–liquid equilibrium calculation using Peng Robinson equation of state implementation, thermodynamic equilibrium calculation and Newton-Raphson’s method for the successive substitution of the unknown variables. The equal fugacity constraint can be satisfied by obtaining the equilibrium which serves as a criterion for two or more phases to exist at equilibrium. The problem was resolved by searching for a pressure that will satisfy the two constraints. Complex calculation was performed by successively substituting the pressure value estimated by Newton–Raphson’s method at reservoir temperature until the two constraints were satisfied. The BPP values for the eight reservoir sample fluids were within the range of 29.32–308.00 atm with an absolute error deviation ranging from 0.00–4.27 and average percentage error of 0.54%. BPP values were obtained were within the reservoir temperature range of 328.15–398.71 K. This procedure is a potential approach for the estimation of BPP for hydrocarbon mixtures with defined fluid composition irrespective of their composition.